Recombinant Protein Truncation Strategy for Inducing Bactericidal Antibodies to the Macrophage Infectivity Potentiator Protein of Neisseria meningitidis and Circumventing Potential Cross-Reactivity with Human FK506-Binding Proteins - Bielecka, Magdalena K. (Infect Immun, 2015)
A recombinant macrophage infectivity potentiator (rMIP) protein of Neisseria meningitidis induces significant serum bactericidal antibody production in mice and is a candidate meningococcal vaccine antigen. However, bioinformatics analysis of MIP showed some amino acid sequence similarity to human FK506-binding proteins (FKBPs) in residues 166 to 252 located in the globular domain of the protein. To circumvent the potential concern over generating antibodies that could recognize human proteins, we immunized mice with recombinant truncated type I rMIP proteins that lacked the globular domain and the signal leader peptide (LP) signal sequence (amino acids 1 to 22) and contained the His purification tag at either the N or C terminus (C-term). The immunogenicity of truncated rMIP proteins was compared to that of full (i.e., full-length) rMIP proteins (containing the globular domain) with either an N- or C-terminal His tag and with or without the LP sequence. By comparing the functional murine antibody responses to these various constructs, we determined that C-term His truncated rMIP (−LP) delivered in liposomes induced high levels of antibodies that bound to the surface of wild-type but not Δmip mutant meningococci and showed bactericidal activity against homologous type I MIP (median titers of 128 to 256) and heterologous type II and III (median titers of 256 to 512) strains, thereby providing at least 82% serogroup B strain coverage. In contrast, in constructs lacking the LP, placement of the His tag at the N terminus appeared to abrogate bactericidal activity. The strategy used in this study would obviate any potential concerns regarding the use of MIP antigens for inclusion in bacterial vaccines.